Learner Autonomy, Language Learning Strategies and English Language Proficiency of Filipino Senior High School Students - Soliman, Christian; Gorospe, Joanne D. (International Journal of Language and Literary Studies, 2024)
This study assessed students’ knowledge by looking at their learner autonomy in English language learning, the extent of language learning strategies and their English language proficiency. A descriptive method of research was used in this study. The respondents of this study were senior high school students of Magsaysay District during the second semester of the Academic Year 2022-2023. They were selected through a proportional random sampling technique. Several instruments were used by the researcher including the survey questionnaires about learner autonomy in English language learning, the extent of language learning strategies as well as the students’ English language proficiency. It was found that the senior high school students of Magsaysay District have a high level of learner autonomy in English language learning in terms of cognitive, affective motivational, action-oriented and social while moderate in terms of metacognitive. Senior high school students of Magsaysay District have a high level of language learning strategies in terms of compensation, social, metacognitive, cognitive, memory and affective. They have an average level of English language proficiency in terms of grammar, vocabulary and reading comprehension. Findings also showed that there is a significant relationship between learner autonomy in English language learning and language learning strategies, between language learning strategies and English language proficiency. However, learner autonomy in English language learning does not affect English language proficiency. Furthermore, results indicate that cognitive best predicts learning language strategy, as well as English language proficiency and cognitive strategy best predicts English language proficiency. In conclusion, the higher the learner autonomy in English language learning, the higher the extent of language learning strategies and the higher the extent of language learning strategies, the higher the English language proficiency.